Election theory: Alternative voting methods in the Pennsylvania 2022 Senate election. - Justine Sullivan (The Young Researcher, 2023)
have on election outcomes, a gap in knowledge remains pertaining to how these systems will affect partisan vote distribution in multi-party elections. This study utilizes a survey approach modeled after the ballots used in Pennsylvania’s 2022 Senate election in order to determine how voter support for each candidate may change as a result of non-plurality voting methods being used. The findings of this research suggest that although it is subjective to each system, alternative voting in general tends to increase voter support for third-party candidates in comparison to plurality, with anti-plurality voting in particular displaying a significant decrease in third-party support in skewed elections. Additionally, ranked-choice voting was found to be the most popular form of voting among participants, indicating a general sense of dissatisfaction with the standard plurality system. These findings suggest that the implementation of non-plurality voting methods may be used to better represent voter preferences and decrease polarization in U.S. elections.